Personalized hematopoietic stem cell transplantation for inborn errors of immunity - Slatter, Mary; Lum, Su Han (Frontiers in Immunology, 2023)
Patients with inborn errors of immunity (IEI) have been transplanted for more than 50 years. Many long-term survivors have ongoing medical issues showing the need for further improvements in how hematopoietic stem cell transplantation (HSCT) is performed if patients in the future are to have a normal quality of life. Precise genetic diagnosis enables early treatment before recurrent infection, autoimmunity and organ impairment occur. Newborn screening for severe combined immunodeficiency (SCID) is established in many countries. For newly described disorders the decision to transplant is not straight-forward. Specific biologic therapies are effective for some diseases and can be used as a bridge to HSCT to improve outcome. Developments in reduced toxicity conditioning and methods of T-cell depletion for mismatched donors have made transplant an option for all eligible patients. Further refinements in conditioning plus precise graft composition and additional cellular therapy are emerging as techniques to personalize the approach to HSCT for each patient